Formal Shifts Use on Achieving Pragmatic Equivalence in English – Indonesian Translation of KungFu Panda - Lathifah, Syifa'ul; Mujiyanto, Januarius (English Education Journal, 2021)
This study is concerned with the analysis of Catford’s formal shifts use in speech act translation from English into Bahasa Indonesia in Kung Fu Panda movie. The analysis covers the use of level shift and category shift on achieving pragmatic equivalence and how the visual-verbal relation happened along with the pragmatic achievement process. This study took documentation and a questionnaire on collecting the data. In this study, a theory from Baker (1992) was applied to analyze pragmatic equivalence achievement. Moreover, the theory from Halliday (1994) in Martinec and Salway (2005) was used to identify visual-verbal relations. The results of the study depicted (1) the use of level shift and category shift were very needed which led to pragmatic equivalence achievement (95,3%). Based on the target readers and expert raters, (2) the visual-verbal relation helped the translator on target text arrangement by providing the context of which the speech act was being uttered. The visual-verbal relation identified in the Kung Fu Panda movie were exposition (12,7%), enhancement (9,3%), extension (5,3%) and locution relation (72,7%). (3) The translator tended to use category shift dominantly (66,67%) for recreating the most suitable target text that was similar to the source text’s pragmatic meaning.The large identification of visual-verbal relation locutionallowed target and expert readers to perceive the meaning lied in speech act only from the word given.